2018 IEEE International Smart Cities Conference (ISC2) 2018
DOI: 10.1109/isc2.2018.8656753
|View full text |Cite
|
Sign up to set email alerts
|

An Edge Computing Approach to Explore Indoor Environmental Sensor Data for Occupancy Measurement in Office Spaces

Abstract: Human occupancy measurement has become a topic of increasing interest in the past few years, due to the important role it plays in controlling a number of demand-driven applications like smart lighting and smart heating, as well as improving the energy efficiency of these applications in a broader sense. Office occupancy monitoring in commercial buildings can yield huge savings and improvements in terms of thermal, visual, and air quality. However, this is often impeded due to the lack of fine-grained occupanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Another alternative approach to detect occupancy is through statistical analysis. Zemouri et al [ 33 ] compared the performance of Machine Learning to detect occupancy against an algorithm developed using statistical analysis, obtaining accuracies of 0.82 and 0.87, respectively. Although they obtained a higher accuracy using statistical analysis, the authors highlighted two significant drawbacks of this approach: (1) the requirement of expert knowledge in the subject area and knowing the physical properties of the variables measured; (2) the slower and more costly performance of this approach, compared to Machine Learning, due to the manual extraction of features.…”
Section: Resultsmentioning
confidence: 99%
“…Another alternative approach to detect occupancy is through statistical analysis. Zemouri et al [ 33 ] compared the performance of Machine Learning to detect occupancy against an algorithm developed using statistical analysis, obtaining accuracies of 0.82 and 0.87, respectively. Although they obtained a higher accuracy using statistical analysis, the authors highlighted two significant drawbacks of this approach: (1) the requirement of expert knowledge in the subject area and knowing the physical properties of the variables measured; (2) the slower and more costly performance of this approach, compared to Machine Learning, due to the manual extraction of features.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 20 studies [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] were removed due to missing information about the design methodology and the type of sensors used for measuring IAQ parameters (IC4, EC3). In addition, five more studies [ 48 , 49 , 50 , 51 , 52 ] were excluded as they were focused on thermal comfort parameters only or had no relevant details about IAQ sensors (IC2, IC3, EC3). After applying inclusion and exclusion criteria, 40 studies were found eligible for conducting this systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…This functionality allowed the system to work with a smaller number of RSSI datapoints while still being able to detect the indoor location of the user with a high accuracy that was deduced by the authors from the results of their experimental trials that included 15 participants. In addition to the above, recent works in this field have focused on building tailored magnetic maps for smartphones [70,71] and using edge computing approaches to analyze environmental sensor data [72,73] for indoor localization. While a few recent works [74][75][76][77][78][79][80] have investigated approaches for floor detection in the context of indoor localization but the performance characteristics of such systems are not that high to support widescale deployment and real-time implementation of the same.…”
Section: Literature Reviewmentioning
confidence: 99%